Analisis Kelayakan Usahatani Tomat (Lycopersicon Esculentum Mi Ll) di Moeda Tani Farm Kecamatan Alok Kabupaten Sikka - Theofilus Reven Roja; Sarlina Noni; Gabriel Otan Apelabi (Fakultas Pertanian, Universitas Nusa Nipa, 2024)
Tomatoes are one of the horticultural commodities that have high economic value and are widely cultivated by farmers due to their considerable market demand. However, tomatoes are highly perishable and their market prices often fluctuate, which can affect farmers’ income levels. Therefore, a farm feasibility analysis is needed to determine whether tomato farming activities can provide economic benefits. This study aims to determine the feasibility of tomato farming at Moeda Tani Farm, Alok District, Sikka Regency. The research was conducted from February to March 2023. The method used in this study was a quantitative descriptive method. Data collection was carried out through interviews, observation, and documentation. The data sources consisted of primary data obtained directly from respondents, namely the manager and employees of Moeda Tani Farm, and secondary data obtained from related institutions. The data analysis used included analysis of production costs, revenue, income, and business feasibility analysis using the Revenue Cost Ratio (R/C). The results of the study show that the total production cost of tomato farming is IDR 24,780,000 per planting season, consisting of fixed costs and variable costs. The total revenue obtained is IDR 36,000,000, resulting in an income of IDR 11,220,000. The R/C ratio obtained is 1.45 or greater than one. This indicates that tomato farming at Moeda Tani Farm is feasible to operate and provides economic benefits, thus having the potential to be further developed.